The Practice of Tajwid Instruction in Developing Qur’anic Reading Skills at Al-Rahman Witya School, Thailand - Samsidar Samsidar; Khoiriah Barokah; Jarki Harahap (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
Tajwid instruction plays a crucial role in developing students’ Qur’anic reading skills, particularly in improving pronunciation accuracy, fluency, and understanding of recitation rules. However, many students at the basic education level continue to struggle to apply tajwid correctly during Qur’anic reading activities. This study investigates the implementation of tajwid instruction at Al-Rahman Witya School, a private Islamic school located in the socio-religious context of Southern Thailand. The study employs a qualitative descriptive approach, involving classroom observations, in-depth interviews with school leaders and Qur’anic teachers, and documentation of students in grades III to VI. The findings reveal that tajwid instruction is carried out through systematic lesson planning, structured classroom practice, and continuous evaluation. Teachers apply various instructional methods, including talaqqi, classical recitation, drill exercises, individual mentoring, and limited use of audiovisual media to support students’ learning. These approaches help students improve pronunciation accuracy, apply basic tajwid rules more consistently, and increase reading fluency. In addition, tajwid instruction helps strengthen students’ confidence and motivation in reciting the Qur’an. The study also identifies several supporting factors influencing the effectiveness of tajwid learning, including institutional commitment, teacher competence, parental involvement, and the surrounding socio-religious environment that encourages regular Qur’anic practice. The study concludes that well-organized tajwid instruction not only enhances students’ technical recitation skills but also fosters positive learning attitudes and strengthens Qur’anic literacy among elementary-level learners in Islamic educational settings.